Unlocking Capital from Within: Investigating the Impact of Founders’ Human and Social Capital on Entrepreneurial Financing in Swedish Innovation-Oriented Small Enterprises - Lingevik,Gustav; Milde,Daniel (2025)
Abstract Title: More Than Money: Human and Social Capital in Financing Swedish Innovative Small Enterprises. Seminar Date: 03/06 - 2025 Course: Degree Project: New Venture Creation- Entrepreneurship and Innovation, Lund University School of Economics and Management, 15 ECTS Authors: Daniel Milde & Gustav Lingevik Supervisor: Joakim Winborg Keywords: Entrepreneurial finance, Human capital, Social capital, Bridged pecking order theory, Financing decision-making Research Question: How do founders leverage their human and social capital to navigate entrepreneurial financing in highly innovative Swedish small enterprises? Purpose: To investigate how small enterprise founders utilize human and social capital in their financial decision-making processes, and how these forms of capital influence access to and choice of funding sources. Methodology: A qualitative multiple-case study based on eight in-depth semi-structured interviews with founders of innovative Swedish SEs across various industries. Theoretical Framework: The study is grounded in theories of human capital (Becker, 1964), social capital (Bourdieu, 1986), the pecking order theory (Myers & Majluf, 1984) and bridged pecking order theory (Paul Whittam & Wyper, 2007). Findings: The study reveals that founders actively leverage human and social capital to navigate financing in non-linear, context-specific ways. Human capital, shaped through prior experience, self-learning, and strategic reflection, was used to interpret investor alignment, timing, and control implications. Social capital functioned both as an access point and a filter, with founders relying on trust-based networks, warm introductions, and shared values to guide investment decisions. Conclusion: This study demonstrates that financing decisions in highly innovative Swedish small enterprises are not driven solely by capital availability or cost, but by founder-led judgment, relationship-building and strategic alignment. Founders selectively combine elements of the traditional and bridged pecking order logics, using human capital to assess timing and structure, and social capital to access and filter investor relationships. Financing is therefore not only a means of acquiring resources, but a way for founders to define and preserve the identity, control, and long-term trajectory of their ventures. The study contributes to entrepreneurial finance literature by reframing financing as a cognitive and relational process, shaped by founders’ lived experience and strategic intent.
Keywords: Entrepreneurial finance; Human capital; Social capital; Bridged pecking order theory; Financing decision-making.